Analysis of HFE impact of COVID-19 on OHS in construction enterprises - Zhonghong Cao; Junjie Zhu; Zhenzhen Wang (Heliyon)
Human factors are critical to Occupational Health and Safety (OHS) in construction enterprises. However, comprehensive industry-wide recognition remains challenging, underscoring the need for Human Factors Engineering (HFE) research. This study develops an optimized HFE evaluation model based on fundamental HFE principles. Examining COVID-19's significant impact on construction enterprise OHS, this research employs an empirical investigation of 259 cases, utilizing a model that integrates NetLogo's System Dynamics (SD) and Multiple Linear Regression (MLR) to analyze the interactions between human factors and other variables. The findings reveal four key factors influencing human factors: management, material, environmental, and methodological. These factors demonstrate a quadratic parabolic relationship, with peak influence occurring at step 36 of the research period. Twelve of the 20 survey factors exhibit a linear regression relationship with human factors' four sub-factors, with pre-job training (Q9) demonstrating multiple influential interactions. The strongest correlation is between pre-job training (Q9) and living materials (Q14), with a weight coefficient of .325. Psychological counseling (Q8) and living materials (Q14) show a close relationship (weight coefficient .301). Notably, Q9 and empirical prevention materials (Q11) display a negative correlation with a weight coefficient of −.156. This study's practical significance lies in enabling enterprises to identify key HFE control factors and understand critical sub-factors for mitigating COVID-19's adverse impacts.